2020
DOI: 10.3390/tropicalmed5030135
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Study of Toxocara Infection in Honduran Children: Human Seroepidemiology and Environmental Contamination in a Coastal Community

Abstract: (1) Background: Infections caused by Toxocara canis and T. cati are considered zoonoses of global importance. Reports from North and South America indicate that human infections are widespread in both continents, but epidemiological information from Central America is still lacking. (2) Methodology: In the present cross-sectional multi-year study, we aimed to undertake the first seroepidemiological and environmental study on toxocariasis in Honduras. This included the determination of seroprevalence of anti-To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…This trend has also been reported in previous studies [ 31 , 32 ]. It has been hypothesized that males engage in more outdoor activities than females and, therefore, are more likely to be in contact with contaminated soil and dogs [ 33 , 34 ]. However, univariate and multivariate analyses demonstrated that sex was not significantly associated with seropositivity for anti- T.canis IgG antibodies in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This trend has also been reported in previous studies [ 31 , 32 ]. It has been hypothesized that males engage in more outdoor activities than females and, therefore, are more likely to be in contact with contaminated soil and dogs [ 33 , 34 ]. However, univariate and multivariate analyses demonstrated that sex was not significantly associated with seropositivity for anti- T.canis IgG antibodies in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, the seroprevalence of toxocariasis varies widely by climate and geographical region, being generally lower in industrialized temperate countries such as the USA (3.6%) ( Bradbury et al, 2020 ) and China (5.1%) ( Wang et al, 2020 ), and higher in lower-middle-income tropical countries such as Nigeria (92.4%) ( Ikotun et al, 2020 ), Honduras (88.6%) ( Hernández et al, 2020 ), Ghana (62.0%) ( Boyko et al, 2020 ), and Vietnam (59.0%) ( Van De et al, 2020 ). Our study reported a relatively low toxocariasis seroprevalence rate of 2.5% among allergic patients, 80% of whom were non-Kuwaiti residents originating from lower-middle-income South/Southeast Asian tropical countries (i.e., the Philippines, Sri Lanka and Bangladesh).…”
Section: Discussionmentioning
confidence: 99%
“…Such is the case with Chagas disease in Trinidad and Tobago, where despite mounting evidence that Trypanosoma cruzi transmission to humans occurs , the nation is not yet formally recognized as ‘Chagas endemic’ by WHO [ 6 ], and as such, does not receive support to combat the disease. Similarly, toxocariasis and giardiasis are not officially recognized as NTDs by WHO, despite having many of the same characteristics and impacts, not to mention the potential benefits for increased scientific attention, funding, and prioritization that could come with being grouped with the NTDs [ 7 , 8 ]. Finally, as mentioned above, existing eradication approaches for Guinea worm disease have been focused solely on humans; recognition of its zoonotic nature is required to ensure future success [ 5 ].…”
mentioning
confidence: 99%